The re-appreciation of the humanities in contemporary philosophy of science: From recognition to exaggeration? - Coletto, Renato (Koers, 2013)
In the course of the centuries, the ‘reputation’ and status attributed to the humanities underwent different phases. One of their lowest moments can be traced during the positivist period. This article explored the reasons underlying the gradual re-evaluation of the scientific status and relevance of the humanities in the philosophy of science of the 20th century. On the basis of a historical analysis it was argued that on the one hand such recognition is positive because it abolishes an unjustified prejudice that restricted the status of ‘science’ to the natural sciences. On the other hand it was argued that the reasons behind such recognition might not always be sound and may be inspired by (and lead to) a certain relativism harbouring undesired consequences. In the final part of this article (dedicated to Prof. J.J. [Ponti] Venter) a brief ‘postscript’ sketched his evaluation of the role of philosophy.